(untitled) (Revista Electrónica REDINE, 2021)
The scientific journal GACETA DE CIENCIAS VETERINARIAS (GCV) (ISSN 1690-8414) was founded in 1995 by Dr. Gabriel Carreño with the purpose of disseminating research produced by the Institution and collaborators from various latitudes in the field of Veterinary Sciences. GCV was preceded by the technical-scientific journal CIENCIAS VETERINARIAS, created in August 1983 by the concern of a group of professors headed by the Director of the Dr. Atilio Atencio School of the Universidad Centroccidental Lisandro Alvarado(UCLA). This long history of GCV has allowed it to contribute to the development of Science and Technology in priority issues in Veterinary Sciences for the benefit of society, disseminating the results of research in an organized, periodic and systematic way. Outreach areas include veterinary medicine, public health, animal nutrition and production, animal genetics and reproduction, animal microbiology and parasitology, animal physiology and pharmacology, forage and agricultural technology, molecular biology and biotechnology. Indexed / cataloged in Revencyt, Latindex, IVIC Library and Latin American News.